The Majority as Minority: Social Adjustment of White and African American Graduate Students at an Historically Black University - Rosemary B. Closson; Wilma J. Henry (Adult Education Research Conference, 2007)
This research study explores the experience of temporary minorities (White students) (Hall & Closson, 2005) and their social adjustment and experiential learning when in a predominantly Black setting.